2021
DOI: 10.3390/ma14185248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasonication of Functionalized Carbon Nanotubes on the Rheology, Hydration, and Compressive Strength of Portland Cement Pastes

Abstract: The functionalization process usually increases the localized defects of carbon nanotubes (CNT). Thus, the ultrasonication parameters used for dispersing non-functionalized CNT should be carefully evaluated to verify if they are adequate in dispersing functionalized CNT. Although ultrasonication is widely used for non-functionalized CNT, the effect of this dispersing process of functionalized CNT has not been thoroughly investigated. Thus, this work investigated the effect of ultrasonication on functionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Similar trends of increasing the yield stress and viscosity of cement paste with other nanomaterials incorporation besides TiO 2 were previously reported by the authors [ 75 , 76 ] and by other research groups [ 77 , 78 , 79 ]. Specifically for 3DP mixes, Sikora et al [ 24 ] observed that 2% nano-SiO 2 incorporation was enough to increase the yield stress of 3DP mortars by 4.2 times (from 46 to 239 Pa).…”
Section: Resultssupporting
confidence: 89%
“…Similar trends of increasing the yield stress and viscosity of cement paste with other nanomaterials incorporation besides TiO 2 were previously reported by the authors [ 75 , 76 ] and by other research groups [ 77 , 78 , 79 ]. Specifically for 3DP mixes, Sikora et al [ 24 ] observed that 2% nano-SiO 2 incorporation was enough to increase the yield stress of 3DP mortars by 4.2 times (from 46 to 239 Pa).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, a superplasticizer was also employed (MC-PowerFlow, Mc-Bauchemie). A complete characterization of all the materials used in this research can be obtained in previous studies published by the authors [12,[19][20][21]. For the simulated cement pore solution, calcium sulfate dihy-…”
Section: Methodsmentioning
confidence: 99%
“…Although CNTs functionalized with polar groups are more hydrophilic and, therefore, have a better dispersion in water, the dispersion in the cement matrix differs in the presence of a highly alkaline environment [12]. For instance, Zou et al [13] observed different optimal ultrasonication values for CNT dispersion in water (determined by UV-visible spectroscopy) and in a cementitious matrix considering the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, uniform dispersion of the fibers throughout the cementitious matrix is of particularly great significance [6,16,17]. The congregation and nonuniform distribution of fibers in the matrix can compromise the consolidation, mechanical strength, and ductility of UHPC [18,19].…”
Section: Introductionmentioning
confidence: 99%